STRATEGI PENYALURAN DANA PADA LEMBAGA SEDEKAH SERIBU SEHARI (S.3) DI KOTA BUKITTINGGI - Hayati, Syukra; Dewi, Sandra (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2023)
The background of this journal is to see the strategy for channeling one thousand a day alms funds (S.3) in Bukittinggi, whether it is in accordance with the Islamic religion in the way of distribution. The strategy for distributing funds for S.3 is to channel funds to underprivileged people or those who need assistance from S.3. The first source of funds for S.3 is one thousand alms a day by people who want to help people in need, through social media , such as Facebook, WhatsApp, Instagram and the surrounding community. These donors are people who admire and support this S.3 program. The management of the S.3 funds was entrusted to Siti Rahmayanti, who is usually called Ummi Cinto. Funds disbursed from the S.3 Program must be distributed to people in need. The purpose of this research is to find out the strategy for channeling funds to the One Thousand A Day Alms Institution (S.3) in the City of Bukittinggi.